Effects of saline irrigation on soil salt accumulation and grain yield in the winter wheat-summer maize double cropping system in the low plain of North China - Xiu-wei LIU; Til Feike; Su-ying CHEN; Li-wei SHAO; Hong-yong SUN; Xi-ying ZHANG (Journal of Integrative Agriculture, 2016)
In the dominant winter wheat (WW)-summer maize (SM) double cropping system in the low plain located in the North China, limited access to fresh water, especially during dry season, constitutes a major obstacle to realize high crop productivity. Using the vast water resources of the saline upper aquifer for irrigation during WW jointing stage, may help to bridge the peak of dry season and relieve the tight water situation in the region. A field experiment was conducted during 2009–2012 to investigate the effects of saline irrigation during WW jointing stage on soil salt accumulation and productivity of WW and SM. The experiment treatments comprised no irrigation (T1), fresh water irrigation (T2), slightly saline water irrigation (T3: 2.8 dS m−1), and strongly saline water irrigation (T4: 8.2 dS m−1) at WW jointing stage. With regard to WW yields and aggregated annual WW-SM yields, clear benefits of saline water irrigation (T3 & T4) compared to no irrigation (T1), as well as insignificant yield losses compared to fresh water irrigation (T2) occurred in all three experiment years. However, the increased soil salinity in early SM season in consequence of saline irrigation exerted a negative effect on SM photosynthesis and final yield in two of three experiment years. To avoid the negative aftereffects of saline irrigation, sufficient fresh water irrigation during SM sowing phase (i.e., increase from 60 to 90 mm) is recommended to guarantee good growth conditions during the sensitive early growing period of SM. The risk of long-term accumulation of salts as a result of saline irrigation during the peak of dry season is considered low, due to deep leaching of salts during regularly occurring wet years, as demonstrated in the 2012 experiment year. Thus, applying saline water irrigation at jointing stage of WW and fresh water at sowing of SM is most promising to realize high yield and fresh irrigation water saving.